The clinical characteristics of secondary primary tumors in patients with nasopharyngeal carcinoma after intensity-modulated radiotherapy: A retrospective analysis. Issue 45 (November 2016) - Zhao, Wei; Lei, Hao; Zhu, Xiaodong; Li, Ling; Qu, Song; Liang, Xia; Wang, Xiao
Abstract : Abstract: To investigate the clinical characteristics associated with the risk of developing secondary primary tumors (SPTs) in patients with nasopharyngeal carcinoma (NPC) who underwent intensity-modulated radiotherapy (IMRT). Data from 527 patients with biopsy-proven nonmetastatic NPC who were treated with IMRT between January 2007 and December 2011 were analyzed retrospectively. The cumulative incidence of SPTs after IMRT completion was estimated using the Kaplan–Meier method. Intergroup differences in the cumulative incidence were determined using the log-rank test. The Cox proportional hazards regression model was used to confirm the risk factors associated with IMRT-induced SPTs. The median follow-up duration was 45.5 months (range, 4–97 months). Of the 527 patients, 12 (2.3%) developed posttreatment SPTs (9 men, 3 women), 6 of which were located in the irradiation field. SPTs were mostly located in the upper aerodigestive tract (n = 7), head and neck (n = 6), lungs (n = 3), and tongue (n = 2). The 1-, 3-, and 5-year cumulative SPT risk rates were 0.4%, 1.4%, and 3.1%, respectively, and the mean annual growth in cumulative incidence was approximately 0.6%. The 1-, 3-, and 5-year cumulative in-field SPT risk rates were 0.4%, 0.8%, and 1.5%, respectively, and the mean annual growth in the in-field cumulative incidence was approximately 0.3%. Univariate and multivariate analysis revealed that sex, age, clinical stage, chemotherapy, and overall IMRT duration did not significantly affect SPT risk. However, the history of smoking was the independent risk factor associated with SPT. The 5-year SPT incidence among patients with NPC after IMRT is concordant with or lower than that in previous 2-dimensional radiotherapy studies study. Among patients with NPC who underwent IMRT, the upper aerodigestive tract was the most common SPT site, and lung cancer was the most common pathology. Smoking history, but not sex, age, clinical stage, chemotherapy, and overall IMRT duration is the independent risk factor associated with SPT. Additional large-scale studies with longer-term follow-ups are needed to determine risk factors associated with SPT development after IMRT.